2012
DOI: 10.1007/s00405-012-1977-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased percentage of T cells with the expression of CD127 and CD132 in hypertrophic adenoid in children with otitis media with effusion

Abstract: The hypertrophic adenoid may promote chronic suppurative otitis media in children as it fulfills its immune function. The number of lymphocytes in the adenoid and their cooperation in the immune response depend of on their proliferation and migration to the effector sites. Interleukin 7 (IL-7) is essential for the normal development and function lymphocytes. IL-7 plays pivotal role for activation and proliferation of T and B cells. The heterodimeric interleukin-7 receptor (IL-7R) is composed of the IL-7Rα (127… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Nowadays, increasing evidence indicates that adenoid immune dysfunction may induce and even aggravate SOM, but the exact mechanism is still not well defined. [ 13 ] In this study, we aim to investigate the roles of Tfh in the pathogenesis of SOM combined with AH. Our study contributed to the early screening and treatment of SOM combined with AH.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, increasing evidence indicates that adenoid immune dysfunction may induce and even aggravate SOM, but the exact mechanism is still not well defined. [ 13 ] In this study, we aim to investigate the roles of Tfh in the pathogenesis of SOM combined with AH. Our study contributed to the early screening and treatment of SOM combined with AH.…”
Section: Introductionmentioning
confidence: 99%
“…OX40, also known as CD134, is a member of the superfamily of TNF receptors; which belongs to the type I transmembrane protein. OX40 was initially found on activated CD4 + T cells ( 8 , 9 ), but subsequent studies reported that OX40 is also expressed on activated CD8 + T cells and neutrophils ( 8 , 10 ). OX40 expression levels on naive CD4 cells peaked 2–3 days after T-cell receptor (TCR) stimulation, and were downregulated 4–5 days after the initial TCR stimulation ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that although there were no significant differences in immunoglobulin levels, patients treated with allergen immunotherapy had lower numbers of FOXP3 + lymphocytes than patients that were not treated ( 16 ). The percentage of T lymphocyte with IL-7R (CD127 and CD132) increased in hypertrophic adenoid, which appeared to influence the number and function of lymphocytes in tonsils; and further influenced the course of chronic otitis media with effusion ( 10 ). The decline of memory T cells was considered a risk factor of chronic otitis media with effusion in adolescents ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-7 plays a pivotal role for activation and proliferation of T and B cells, with IL-7R (CD127 and CD132) expression an important marker of immunologic function. Evaluation of CD4 1 and CD8 1 T cells in AH of older children suffering with OME for 3 months or without OME 74 found that the percentages of CD4 1 and CD8 1 CD127 receptor and CD4 1 CD132 expression but not CD8…”
Section: Adaptive Immunitymentioning
confidence: 99%